A Theoretical Model for the Size Prediction of Single Bubbles Formed under Liquid Cross-flow - 刘长军 梁斌 唐盛伟 张海广 闵恩泽 (Chinese journal of chemical engineering, 2010)
The size of initial bubbles is an important factor to the developed bubble size distribution in a gas-liquid contactor. A liquid cross-flow over a sparger can produce smaller bubbles, and hereby enhance the performance of contactor. A one stage model by balancing the forces acting on a growing bubble was developed to describe the formation of the bubble from an orifice exposed to liquid cross-flow. The prediction with this model agrees with the experimental data available in the literatures, and show that orifice size strongly affects the bubble size. It is showed that the shear-lift force, inertia force, surface tension force and buoyancy force are major forces, and a simplified mathematical model was developed, and the detachment bubble diameter can be predicted with accuracy of ±21%.